2012
DOI: 10.14710/jil.10.1.19-25
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Jenis Pohon Lokal Cepat Tumbuh Untuk Pemulihan Lahan Pascatambang Batubara (Studi Kasus Di Pt. Singlurus Pratama, Kalimantan Timur)

Abstract: Reclamation efforts in the mining business in the District

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
0
12
0
9
Order By: Relevance
“…Akbar et al (2005) identified 11−16 understorey and seedling species under stands growing on the reclaimed areas of two coalmining companies in South Kalimantan. Adman et al (2012) recorded 58 plant species on the pre-coal-mining area in East Kalimantan. Solviana et al (2012) found 6 seedling species and 43 sapling species on the pre-coal-mining area, but 5 seedling species and 10 sapling species on the post-coalmining area in West Sumatera.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akbar et al (2005) identified 11−16 understorey and seedling species under stands growing on the reclaimed areas of two coalmining companies in South Kalimantan. Adman et al (2012) recorded 58 plant species on the pre-coal-mining area in East Kalimantan. Solviana et al (2012) found 6 seedling species and 43 sapling species on the pre-coal-mining area, but 5 seedling species and 10 sapling species on the post-coalmining area in West Sumatera.…”
Section: Resultsmentioning
confidence: 99%
“…Few plants are able to live in or adapt to the marginal land. Some of such pioneer plants are Macaranga trichocarpa, Homalanthus populneus, Mallotus paniculatus, and Trema orientalis (Kiyono & Hastaniah 2000), Macaranga gigantea and M. hypoleuca (Edwar et al 2011), Calliandra callothyrsus (Darmawan & Anggraeni 2011;Mukhtar & Heriyanto 2012), Acacia mangium (Krisnawati et al 2011a), P. falcataria (Krisnawati et al 2011b), Vitex pinnata (Nugroho & Adman 2011;Mukhtar & Heriyanto 2012), Hevea brasiliensis (Tistama et al 2009;Tjahyana & Ferry 2011), and M. gigantea (Adman et al 2012). Those plants found in the sampling plots/squares grew naturally, except C. callothyrsus and P. falcataria including H. brasiliensis which were proposely planted and found on Location 2 but in a single individual.…”
Section: Resultsmentioning
confidence: 99%
“…Pada umumnya lahan bekas penambangan memiliki kandungan hara makro yang sangat rendah, terutama kandungan N, P, K, Na dan Ca, serta tingkat kemasaman tanah pH dan Kapasitas Tukar Kation (KTK) yang rendah. Selain itu mikroorganisme tanah yang sangat membantu dalam stabilisasi struktur tanah, sumbangan mineral-mineral inorganik, ataupun sumbanganya dalam zat pengatur pertumbuhan, juga sangat rendah [5] .…”
Section: Pendahuluanunclassified
“…The resource‐rich province of East Kalimantan, on the island of Borneo, is Indonesia's primary coal producer and coal is an economic driver in the province (Fünfgeld, ). These economic benefits, however, come at great cost to human and environmental health and threaten biodiversity conservation in one of the world's richest biodiversity hotspots (Adman, Hendrarto, & Sasongko, ; Rinaldi & Yassir, ). Concern over the dangers of abandoned mines have led to policy changes that require coal companies to engage in ecological restoration (revegetation) to rehabilitate abandoned mines (Rinaldi & Yassir, ).…”
Section: Introductionmentioning
confidence: 99%
“…In East Kalimantan, plantation forests are used to facilitate the restoration of native forest on post‐coal mine lands (Adman et al, ; Rinaldi & Yassir, ). Many studies have demonstrated that tree plantations can establish, ameliorate harsh environmental conditions, and facilitate succession of native secondary forest on degraded tropical landscapes (Ashton et al, ; Kuusipalo et al, ; Lamb et al, ; Otsamo, ; Parrotta, ; Parrotta et al, ).…”
Section: Introductionmentioning
confidence: 99%